2021
DOI: 10.1186/s12967-021-02715-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive monitoring of pH and oxygen using miniaturized electrochemical sensors in an animal model of acute hypoxia

Abstract: Background One of the most prevalent causes of fetal hypoxia leading to stillbirth is placental insufficiency. Hemodynamic changes evaluated with Doppler ultrasound have been used as a surrogate marker of fetal hypoxia. However, Doppler evaluation cannot be performed continuously. As a first step, the present work aimed to evaluate the performance of miniaturized electrochemical sensors in the continuous monitoring of oxygen and pH changes in a model of acute hypoxia-acidosis. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
5
1
Order By: Relevance
“…Previous studies with electrochemical sensors were designed similar to those used in this study demonstrated different sensibilities. In an adult rabbit model with a ventilatory hypoxia induction, the pO 2 electrochemical sensor inserted in the skeletal muscle presented lower sensibility in comparison with the sensibility described here [12]. These differences may be explained with different reasons.…”
Section: Electrochemical Sensorscontrasting
confidence: 57%
See 2 more Smart Citations
“…Previous studies with electrochemical sensors were designed similar to those used in this study demonstrated different sensibilities. In an adult rabbit model with a ventilatory hypoxia induction, the pO 2 electrochemical sensor inserted in the skeletal muscle presented lower sensibility in comparison with the sensibility described here [12]. These differences may be explained with different reasons.…”
Section: Electrochemical Sensorscontrasting
confidence: 57%
“…This could be because acidosis produced in the tissue by cells affected by hypoxia takes some time to reach the blood flow, producing a delay in the response in blood-based measurement. Finally, as observed with the oxygen sensor, the sensibilities observed for the pH sensing differ from a previous study [12]. Again, these differences may be explained by the same three reasons as discussed above on the differences observed with the oxygen sensor.…”
Section: Electrochemical Sensorssupporting
confidence: 47%
See 1 more Smart Citation
“…The low oxygen in tissue causes acute and chronic hypoxia, which induces low oxygen in the blood called hypoxemia. This finally results in an acidosis condition (low blood pH) [ 10 ].…”
Section: Fetal Acidosismentioning
confidence: 99%
“…Apart from pH, a few other parameters have been observed to change significantly during acidosis. In study [ 10 ], it was noticed that , pH and bicarbonate concentrations decreased, whereas lactate and potassium concentrations increased. However, was the parameter that most quickly reflected changes in the acid-base status, reaching its minimum value within 2.38 min.…”
Section: Fetal Acidosismentioning
confidence: 99%